Changing environmental conditions and applying organic fertilizers in Origanum vulgare L. - Murillo-Amador, Bernardo; Morales-Prado, Luis E.; Troyo-Diéguez, Enrique; Córdoba-Matson, Miguel V.; Hernández-Montiel, Luis G.; Rueda-Puente, Edgar O.; Nieto-Garibay, Alejandra (Frontiers in Plant Science, 2015)
Any improvement in agricultural systems that results in higher production should also reduce negative environmental impacts and enhance sustainability. The aim of this research was to investigate the effect of two different production systems, one open-field and the other shade-enclosure with four bocashi doses, in order to find the best environmental option in terms of yield, physiological and morphometric characteristics in one oregano (Origanum vulgare L.) cultivar. In this study a completely randomized block design was used with four replications and evaluated for photosynthetic and transpiration rate, stomatal conductance, chlorophyll, leaf area and temperature, aerial and roots fresh and dry biomass, fresh and dry yield. The results showed that oregano adapted best to the shade-enclosure with increase yield of fresh and dry leaf weight of 165% and 118%, respectively, when compared to open-field. Also, higher doses of bocashi improved yield in both environments but more so in shade-enclosure. Soil moisture retention was higher in shade-enclosure which was reflected in physiological variables for soil matric potential, transpiration, stomatal conductivity, photosynthesis being significantly higher in shade-enclosure compared to open-field, thus improving yield. It seems that oregano plants can be grown and perform better under shade-enclosure than open-field and bocashi is a suitable organic fertilizer.